High Performance Wide Angle DBR Design for Optoelectronic Devices - Ting Zhi; Tao Tao; Bin Liu; Yu Yan; Zili Xie; Hong Zhao; Dunjun Chen (IEEE Photonics Journal)
To improve the performance of optoelectronic devices, a high performance wide angle SiO2/Ti3O5 Distributed Bragg Reflector (DBR) mirror was designed and fabricated on double polished sapphire substrate. 17-pairs gradually varied DBR structure was applied in order to acquire a broad stopband reflectivity over 95% from 400 nm to 800 nm, covering the whole visible light region. The DBR mirrors deposited at the backside of optoelectronics devices are also demonstrated to remain a high reflectivity at wide incident angles, which improves the emission efficiency of LEDs and light absorption efficiency of InGaN/GaN photoelectrochemical cell (PEC).